Perancangan Desain UI/UX Aplikasi Mobile Defisit Kalori Menggunakan Metode Design Thinking - Wuisang, Metty; Mambu, Joe Yuan; Maringka, Raissa (Journal of Information System Research (JOSH), 2024)
The increasing prevalence of lifestyle-related health issues highlights the necessity for innovative solutions to promote healthier habits. This study aims to design a better and more suitable user interface (UI) for the user experience (UX) of a mobile calorie deficit application using the Design Thinking method. The primary objective is to create a user-centric UI design that enhances user engagement and supports weight management goals. Through a comprehensive Design Thinking process, which includes empathizing with users, defining problems, ideating solutions, prototyping, and testing, we developed a UI design tailored to the needs of individuals seeking to manage their calorie intake effectively. The testing phase involved two scenarios. The first scenario achieved a miss click rate of 0-9% and a usability score ranging from 91 to 100. User feedback was continuously integrated to refine the design, ensuring usability and functionality. The results demonstrate that the well-structured UI design effectively improves user satisfaction and interaction. This research underscores the value of Design Thinking in developing user-centered interfaces for health management applications.